Factors associated with elevated alanine aminotransferase in employees of a German chemical company: results of a large cross-sectional study - Claus, Matthias; Antoni, Christoph Helmer; Hofmann, Bernd (BMC gastroenterology, 2021)
We aimed to determine the prevalence of elevated alanine aminotransferase (eALT) in employees of a German chemical company, and analyze its association with sociodemographic, work- and lifestyle-related factors.